2014
DOI: 10.1148/radiol.13130039
|View full text |Cite
|
Sign up to set email alerts
|

Synovitis in Patients with Early Inflammatory Arthritis Monitored with Quantitative Analysis of Dynamic Contrast-enhanced Optical Imaging and MR Imaging

Abstract: Quantitative analysis of contrast-enhanced optical imaging allows for potential therapeutic monitoring of synovitis in patients with inflammatory arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 47 publications
3
34
0
4
Order By: Relevance
“…Optical fluorescence imaging as a non-ionizing, fast, and costefficient imaging modality has also been considered in planar mode for the evaluation and monitoring of labelled cells [42,43]. However, planar imaging methods do not resolve fluorescence signals emanating from different depths, but instead deliver a weighted projection of the fluorochrome distribution, a fact that limits sensitivity and quantitative accuracy [44].…”
Section: Discussionmentioning
confidence: 99%
“…Optical fluorescence imaging as a non-ionizing, fast, and costefficient imaging modality has also been considered in planar mode for the evaluation and monitoring of labelled cells [42,43]. However, planar imaging methods do not resolve fluorescence signals emanating from different depths, but instead deliver a weighted projection of the fluorochrome distribution, a fact that limits sensitivity and quantitative accuracy [44].…”
Section: Discussionmentioning
confidence: 99%
“…Meier et al (95) published their work on use of dynamic contrastenhanced optical imaging to monitor therapy for inflammatory arthritis in Radiology in 2014. They showed that quantitative analysis of contrast-enhanced optical imaging enables potential therapeutic monitoring of synovitis in the hands of patients with inflammatory arthritis (95).…”
Section: Sodium Imagingmentioning
confidence: 99%
“…Since hypoxia affects both tissue blood content and oxygenation [22,24], near-infrared optical methods-diffuse optical spectroscopy (DOS) and tomography (DOT), and photoacoustic tomography (PAT)-that are sensitive to these physiological parameters are being developed to supplement/replace clinical assessment and radiology for RA monitoring [25][26][27][28][29][30][31][32][33][34]. These emerging techniques, DOS in particular, have the potential to overcome most of the limitations of current RA monitoring methods since they are safe, relatively inexpensive, and have the potential to quickly and objectively assess RA inflammation at the individual joint level [34,35]. Early applications were limited to measuring joint optical properties at a single wavelength and applying classification algorithms to distinguish inflamed from healthy joints [36][37][38].…”
Section: Introductionmentioning
confidence: 99%